2017
DOI: 10.1155/2017/4923426
|View full text |Cite
|
Sign up to set email alerts
|

A Ligation of the Lacrimal Excretory Duct in Mouse Induces Lacrimal Gland Inflammation with Proliferative Cells

Abstract: The lacrimal gland secretes tear fluids to ocular surface, which plays an indispensable role in maintaining the health of the ocular epithelia and protecting the ocular surface from the external environment. The dysfunction of the lacrimal glands causes dry eye disease due to a reduction in tear volume. The dry eye disease is becoming a popular public disease, for the number of patients is increasing, who have subjective symptom and loss of vision, which affect the quality of life. Inflammatory change in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The ligated artery supplies approximately 60% of blood flow to the LG in the normal state; the remaining blood supply was maintained. 24 This model exhibited a proliferative state after inflammation, which is consistent with the previous partial injury model of LGs. Similar to the rabbit model, immunohistochemical analysis showed that nestin þ cells were significantly increased in the interstitial tissues with an elongated morphology after surgery.…”
Section: For Review)supporting
confidence: 90%
See 3 more Smart Citations
“…The ligated artery supplies approximately 60% of blood flow to the LG in the normal state; the remaining blood supply was maintained. 24 This model exhibited a proliferative state after inflammation, which is consistent with the previous partial injury model of LGs. Similar to the rabbit model, immunohistochemical analysis showed that nestin þ cells were significantly increased in the interstitial tissues with an elongated morphology after surgery.…”
Section: For Review)supporting
confidence: 90%
“…In the salivary gland, the ductal ligation model induced the proliferation of various cell types, including acinar, ductal, and myoepithelial cells, during tissue repair after ligature release. 23 Recently, two studies 24,25 have been reported regarding LG dysfunction in animal models (murine and rabbit) by ductal ligation. Both studies show that the ligation-injured LGs decrease in size and weight dramatically and exhibit impaired tear secretion with inflammatory cell infiltration.…”
Section: For Review)mentioning
confidence: 99%
See 2 more Smart Citations
“…temporary period of inflammation and apoptosis, tissue repair processes occur through the induction of proliferative cells expressing the stem cell markers Nestin, Ki67, ABCG2, and Sca-1. 52,54 Interstitial cells with mesenchymal cell markers, subsets of cells expressing muscle-related proteins, and epithelial mesenchymal transition pathways have also been suggested as contributing to repair processes. 55 Recent studies have revealed characteristics of the tissue stem/progenitor cells in the lacrimal glands.…”
Section: Identification Of Tissue Stem/progenitor Cells In the Lacrimmentioning
confidence: 99%